Gel polymer electrolyte diaphragm, preparation method and zinc ion battery

By introducing two-dimensional polymer carboxylate into the gel electrolyte separator, its mechanical properties and ionic conductivity are improved, the problem of dendrite growth and hydrogen evolution reaction of zinc ion batteries during the charge and discharge cycle is solved, and the cycle life of the battery is extended.

CN119674434AActive Publication Date: 2025-03-21ANHUI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411791174.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-21
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The poor mechanical properties of existing gel electrolyte separators lead to zinc ion batteries being prone to dendrite growth and hydrogen evolution reactions during the charge and discharge cycle, reducing Coulomb efficiency and cycle life.

Method used

By blending the two-dimensional polymer carboxylate with hydrophilic monomer, adding a crosslinker and an initiator, a gel polymer electrolyte separator is reacted under light conditions to form a gel polymer electrolyte separator, which improves the mechanical properties and ionic conductivity of the separator.

Benefits of technology

It improves the mechanical properties and ionic conductivity of the gel polymer electrolyte separator, enhances its self-healing ability, effectively inhibits the generation of dendrites and hydrogen evolution reaction, and extends the cycle life of zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674434A_ABST
    Figure CN119674434A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a gel polymer electrolyte diaphragm, which comprises the following steps: blending two-dimensional polymer carboxylate with a hydrophilic monomer, adding a cross-linking agent and a first initiator into the mixture, and reacting under an illumination condition to obtain a thin film; and dialyzing and soaking the thin film to prepare the gel polymer electrolyte diaphragm. The preparation method of the two-dimensional polymer carboxylate comprises the following steps: carrying out substitution reaction on 3, 5-diaminobenzoic acid and acryloyl chloride to obtain a monomer DBA; p-aminobenzoic acid and acryloyl chloride are subjected to a substitution reaction, and a monomer ADA is obtained; and mixing the monomer DBA with the monomer ADA, adding organic alkali and a second initiator into the mixture, and carrying out polymerization reaction to prepare the two-dimensional polymer carboxylate. The gel polymer electrolyte diaphragm is generated through blending reaction of the synthesized two-dimensional polymer carboxylate and the hydrophilic monomer, stronger ionic interaction is brought by introduction of the two-dimensional polymer carboxylate, and the mechanical property of the diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a gel polymer electrolyte diaphragm and a preparation method thereof, and a zinc ion battery. Background Art

[0002] Zinc-ion batteries have attracted extensive research due to their inherent green safety, low price, and abundant reserves. The metallic zinc anode has a high theoretical capacity (820mAh / g) and a lower redox potential (-0.76V) than the standard hydrogen electrode. However, during the charge and discharge cycle, the zinc electrode is easily corroded, producing zinc dendrites and byproducts produced by the hydrogen evolution reaction, resulting in reduced Coulombic efficiency, shortened cycle life, and even battery short circuit. In addition, the problem of easy leakage of liquid electrolytes also poses a huge safety hazard, limiting its commercial application. In order to overcome these obstacles, people have developed a variety of strategies, such as optimizing the electrolyte composition, zinc anode surface coating, and constructing ion transfer channels. In addition, the design of new diaphragms is also considered to be a simple but effective strategy to improve battery stability.

[0003] Glass fiber (GF) separator is the most commonly used separator in aqueous batteries. However, most GF separators have large but uneven pores and lack zinc-philic groups. This is not conducive to the Zn 2+ The uniform distribution and desolvation of Zn lead to the crazy growth of Zn dendrites and the generation of hydrogen evolution reaction. To date, various modification strategies of GF membranes have been reported to protect the zinc anode. For example, a component with a large number of polar groups is introduced into the GF membrane to absorb Zn 2+ , which can avoid Zn 2+ The uneven deposition on the surface of zinc anode inhibits the formation of zinc dendrites. Adding ion sieves with uniform micro / mesoporous ion channels to the GF separator can regulate the zinc plating / stripping, so that zinc can be uniformly deposited on the anode. However, the above strategy fails to solve the problem of poor mechanical properties inherent in the GF separator itself, so dendrites can easily puncture the separator when growing, causing battery short circuit.

[0004] Gel electrolyte (GPE) separator is one of the effective means to solve the above problems. Gel polymer electrolyte separator is a quasi-solid electrolyte separator composed of a hydrophilic polymer chain network and a saline solution. It not only has a solid structure similar to that of a solid electrolyte, but also has a higher ionic conductivity near an aqueous electrolyte. Although GPE separators are superior to aqueous electrolytes in some aspects, they also have the following problems: the low ionic conductivity of GPE separators leads to their higher overpotential, the poor affinity with the electrode increases the interfacial impedance of the electrolyte-electrode interface, and the poor mechanical properties hinder their widespread application in wearable devices. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to improve the mechanical properties of the gel electrolyte.

[0006] The present invention solves the above technical problems through the following technical means:

[0007] The first aspect of the present invention provides a method for preparing a gel polymer electrolyte membrane, comprising the following steps: blending a two-dimensional polymer carboxylate with a hydrophilic monomer, adding a crosslinking agent and a first initiator thereto, reacting under light conditions to obtain a film; dialyzing and soaking the film to obtain a gel polymer electrolyte membrane; the method for preparing the two-dimensional polymer carboxylate is as follows: subjecting 3,5-diaminobenzoic acid to a substitution reaction with acryloyl chloride to obtain a monomer DBA; subjecting p-aminobenzoic acid to a substitution reaction with acryloyl chloride to obtain a monomer ADA; mixing the monomer DBA with the monomer ADA, adding an organic base and a second initiator thereto to carry out a polymerization reaction to obtain the two-dimensional polymer carboxylate.

[0008] Beneficial effects: The two-dimensional polymer carboxylates synthesized by the present invention have a hydrophobic-hydrophilic layered structure and a high specific surface area; the present invention generates a gel polymer electrolyte membrane by a blending reaction of the synthesized two-dimensional polymer carboxylates and hydrophilic monomers, and the introduction of the two-dimensional polymer carboxylates brings about stronger ion interactions, improves the mechanical properties of the membrane, and also brings about a certain self-healing ability, and when the gel polymer electrolyte membrane is punctured by dendrites, it has a certain recovery ability; the present invention introduces the two-dimensional polymer carboxylates into the gel polymer electrolyte membrane, brings about abundant carboxylate groups, can reduce the hydration degree of zinc ions, and effectively inhibit the hydrogen evolution reaction.

[0009] Preferably, the hydrophilic monomer includes a cationic monomer and an anionic monomer, the cationic monomer includes one of acryloyloxyethyltrimethylammonium chloride, acrylamidomethylpropane sulfonic acid and vinylpyridine; the anionic monomer includes one of sodium styrene sulfonate and 2-acrylamido-2-methylpropane sulfonic acid.

[0010] Beneficial effects: The present invention forms a long-range ordered anion and cation transfer channel through the functional group action between carboxylate and ammonium and sulfonate, which can achieve higher ion transmission in the battery, improve ion conductivity, and is conducive to uniform deposition of ions and inhibition of dendrite generation; in addition, the introduced zinc-philic group carboxylate is conducive to the contact between the gel electrolyte and the zinc electrode, reducing the interface impedance of the electrolyte-electrode interface.

[0011] Preferably, the crosslinking agent includes one of divinylbenzene, diisocyanate and N,N-methylenebisacrylamide.

[0012] Preferably, the first initiator includes one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0013] Preferably, the organic base is 1,1,3,3-tetramethylguanidine; and the second initiator is potassium persulfate.

[0014] Preferably, the cross-linking agent accounts for 0.5% of the mass of the hydrophilic monomer.

[0015] Preferably, the first initiator accounts for 0.8% of the mass of the hydrophilic monomer.

[0016] Preferably, the illumination condition is ultraviolet light with a wavelength of 365 nm.

[0017] The second aspect of the present invention provides a gel polymer electrolyte membrane, which is prepared according to the above-mentioned method for preparing the gel polymer electrolyte membrane.

[0018] Beneficial effects: The gel polymer electrolyte membrane of the present invention has good mechanical properties, high ion conductivity, good anion and cation transfer channels and certain self-healing ability, which can improve the battery cycle life; there is a strong interaction force between the functional groups in the gel polymer electrolyte membrane and water, which reduces the hydration degree of zinc ions, effectively inhibits the hydrogen evolution reaction, and improves the battery cycle life.

[0019] The third aspect of the present invention provides a zinc ion battery, comprising a positive electrode, a separator and a negative electrode, wherein the separator is the above-mentioned gel polymer electrolyte separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of monomer DBA in the embodiment;

[0021] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of monomer ADA in the embodiment;

[0022] Figure 3 is a hydrogen nuclear magnetic resonance spectrum of a two-dimensional polymer carboxylate in the embodiment;

[0023] Figure 4 1 is a stress-strain curve of the gel polymer electrolyte membrane of Example 1, the electrolyte membrane of Comparative Example 1 and the commercial membrane of Comparative Example 2, wherein the gel polymer electrolyte membrane is named PNDP, the electrolyte membrane is named PND, and the commercial membrane is named GF;

[0024] Figure 5 is a graph showing the self-healing performance of the gel polymer electrolyte membrane of Example 1;

[0025] Figure 6The AC impedance spectra of the gel polymer electrolyte membrane of Example 1, the electrolyte membrane of Comparative Example 1 and the commercial membrane of Comparative Example 2 are shown; wherein the gel polymer electrolyte membrane is named PNDP-1, the electrolyte membrane is named PND, and the commercial membrane is named GF;

[0026] Figure 7 The gel polymer electrolyte membrane of Example 1, the electrolyte membrane of Comparative Example 1 and the commercial membrane of Comparative Example 2 were assembled into a zinc ion battery at 1 mA / cm 2 Constant current charge and discharge curves at current density of ; the gel polymer electrolyte membrane is named PNDP, the electrolyte membrane is named PND, and the commercial membrane is named GF;

[0027] Figure 8 The gel polymer electrolyte membrane of Example 1 is assembled into a zinc ion battery at 1 mA / cm 2 SEM image of the zinc negative electrode surface after cycling for 200h at a current density of;

[0028] Fig. 9 The electrolyte membrane of Example 1 is assembled into a zinc ion battery at 1 mA / cm 2 SEM image of the zinc negative electrode surface after cycling for 200h at a current density of;

[0029] Fig.10 The commercial separator of Example 2 is assembled into a zinc ion battery at 1 mA / cm 2 SEM image of the zinc negative electrode surface after cycling for 200 h at a current density of . DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0032] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0033] Example 1

[0034] This embodiment provides a method for preparing a gel polymer electrolyte membrane, which specifically includes the following steps:

[0035] 1. Preparation of Two-Dimensional Polymer Carboxylates

[0036] (1) Weigh 3,5-diaminobenzoic acid (250g, 1.64mol) and add it to a 2L pear-shaped bottle, then add 4L potassium carbonate (680g, 4.92mol) aqueous solution, and after stirring for 1h, slowly add acryloyl chloride (335ml, 4.10mol) in an ice-water bath. After the addition is complete, warm the temperature to room temperature and react for 4h. After the reaction is completed, adjust the mixed system with dilute hydrochloric acid (PH<3) to produce a large amount of precipitate. Let it stand for a while and then filter it. Then wash the filter cake until the solution becomes colorless, put it in a refrigerator to freeze, and then place it in a freeze dryer for 2 days to remove the solvent in vacuum to obtain the target small molecule monomer DBA. Its nuclear magnetic resonance hydrogen spectrum is as follows Figure 1 shown.

[0037] (2) Weigh p-aminobenzoic acid (274 g, 2 mol) and place it in a 2L beaker. Add NaOH (160 g, 4 mol) aqueous solution. After it is completely dissolved, place it in an ice water bath. Gradually add acryloyl chloride (244 ml, 3 mol). While adding, touch the wall of the cup to see the temperature change. Stop adding when the temperature rises, and continue adding after the temperature drops. After the addition is complete, remove the ice water bath and react at room temperature for 12 hours. After the reaction is completed, slowly add 12M hydrochloric acid to acidify the reaction solution to acidity. A large amount of white solid precipitates. The filter cake obtained by suction is washed with pure water until the solution is neutral. Finally, the filter cake is placed in a freeze dryer to dry to obtain a white solid, which is monomer ADA. Its hydrogen nuclear magnetic resonance spectrum is as follows Figure 2 shown.

[0038] (3) Weigh the monomer DBA (125 mg, 0.48 mmol) and the monomer ADA (92 mg, 0.48 mmol) into a 10 ml polymerization tube, add them into 2.2 ml of deionized water and ultrasonically disperse them for 20 min to obtain a gray suspension. Then, 242 uL of organic base 1,1,3,3-tetramethylguanidine is added to the suspension. The suspension immediately becomes clear and transparent. Initiator potassium persulfate (7.8 mg, 0.029 mmol) is added thereto. The air is removed by freezing with liquid nitrogen, and then the tube is thawed and filled with nitrogen. The operation is repeated three times. After the polymerization, place the mixture in an oil bath and heat it to 40°C. Prepare an aqueous solution of sodium thiosulfate (3.8 mg, 0.025 mmol) and inject it into a 10 ml polymerization tube using a microinjector. Polymerize at 40°C for 12 hours. After the polymerization, dialyze it for 48 hours using a dialysis bag with a molecular weight cutoff of 8000-14000. Change the water 8-12 times during the period. Take the polymer dialysate and freeze-dry it in a freeze dryer for 72 hours to obtain a purple solid. The purple solid is the two-dimensional polymer carboxylate. The hydrogen nuclear magnetic resonance spectrum of the two-dimensional polymer carboxylate is as follows: Figure 3 As shown, the double bond disappears completely, indicating that the polymerization is successful.

[0039] 2. Preparation of Gel Polymer Electrolyte Separator

[0040] (4) Weigh the cationic monomer acryloyloxyethyl trimethylammonium chloride (200 mg, 1.03 mmol), the anionic monomer sodium styrene sulfonate (200 mg, 0.96 mmol) and 2 mg of the cross-linking agent N,N-methylenebisacrylamide into a 5 ml centrifuge tube, add 1000 ml of deionized water, shake and ultrasonically mix, add 5 mg of the two-dimensional polymer carboxylate prepared in step (3), shake and ultrasonically mix, add 3.2 mg of the photoinitiator 2-hydroxy-2-methyl-1-phenylacetone, shake and mix, pour into a polytetrafluoroethylene plate, and polymerize under an ultraviolet lamp with a wavelength of 365 nm for 0.5 h. After the polymerization reaction is completed, remove the diaphragm from the polytetrafluoroethylene plate and dialyze in deionized water for 24 h, during which the water is replaced 8-12 times to ensure that the sodium chloride is completely removed. After dialysis, soak in a 2 mol / L zinc sulfate solution for 24 h, during which the zinc sulfate solution is replaced 4-5 times, to finally obtain a gel polymer electrolyte membrane.

[0041] Figure 4 is the stress-strain curve of the gel polymer electrolyte membrane of this embodiment, named PNDP. Figure 4 It can be seen that the stress is as high as 1.8MPa and the strain is close to 500%, indicating that the gel polymer electrolyte membrane has good mechanical properties.

[0042] Figure 5 is the self-healing performance diagram of the gel polymer electrolyte membrane of this embodiment. Figure 5 It can be seen that the gel polymer electrolyte membrane is cut into two sections and dyed with methyl orange and methylene blue respectively. After 2 hours, the two sections are healed together and can be folded and bent, which shows that the gel polymer electrolyte membrane has a certain self-healing ability. When the gel polymer electrolyte membrane is punctured by dendrites, it has a certain recovery ability, which can improve the battery cycle life.

[0043] Figure 6 is the AC impedance spectrum of the gel polymer electrolyte membrane of this embodiment, named PNDP-1. Figure 6 It can be seen that the gel polymer electrolyte membrane can be tested by clamping it with a stainless steel gasket. The thickness of the membrane is 0.0566 cm and the resistance is 17.3 Ω. After calculation, the conductivity of the gel polymer electrolyte membrane is 1.7 x 10 -3 S / cm.

[0044] 3. Preparation of zinc ion batteries

[0045] (5) The gel polymer electrolyte membrane obtained in step (4) is placed on a clean polytetrafluoroethylene plate and naturally air-dried until the water content is less than 30%. After the drying, the gel polymer electrolyte membrane is cut into 14 mm discs and assembled into zinc ion batteries for relevant electrochemical tests. The assembly order is: negative electrode shell, zinc sheet, gel polymer electrolyte membrane, zinc sheet, gasket, spring sheet, positive electrode shell.

[0046] Figure 7 The gel polymer electrolyte separator of this embodiment is assembled into a zinc ion battery at 1 mA / cm 2 The constant current charge and discharge curves tested under the current density of Figure 7 It can be seen that the voltage polarization is small and stable, and the cycle can be sustained for more than 1000 hours.

[0047] Figure 8 The gel polymer electrolyte membrane of this example is assembled into a zinc ion battery at 1mA / cm 2 The SEM image of the zinc negative electrode surface after cycling for 200h at a current density of Figure 8 It can be seen that zinc ions are uniformly deposited on the surface of the electrode, indicating that the formation of long-range ordered anion and cation transport channels is conducive to the deposition of zinc ions and can effectively inhibit the formation of dendrites.

[0048] Example 2

[0049] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that: the hydrophilic monomers are the same, the cationic monomer is acrylamidomethylpropane sulfonic acid; and the anionic monomer is 2-acrylamido-2-methylpropane sulfonic acid.

[0050] Example 3

[0051] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that: the hydrophilic monomer is different, the cationic monomer is vinyl pyridine; and the anionic monomer is sodium styrene sulfonate.

[0052] Example 4

[0053] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that a different cross-linking agent is used, and diisocyanate is used in this embodiment.

[0054] Example 5

[0055] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that a cross-linking agent is different, and divinylbenzene is used in this embodiment.

[0056] Example 6

[0057] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that the first initiator is different. This embodiment uses 1-hydroxycyclohexyl benzophenone.

[0058] Example 7

[0059] This embodiment provides a method for preparing a gel polymer electrolyte membrane. The difference between this embodiment and embodiment 1 is that the first initiator is different. This embodiment uses 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing an electrolyte membrane. The difference between this comparative example and Example 1 is that no two-dimensional polymer carboxylate is added. The specific preparation method is as follows:

[0062] (1) Weigh 200 mg of acryloyloxyethyl trimethylammonium chloride (1.03 mmol), sodium styrene sulfonate (200 mg, 0.96 mmol) and 2 mg of cross-linking agent N,N-methylenebisacrylamide into a 5 ml centrifuge tube, add 1000 ml of deionized water, shake and ultrasonically mix, add 3.2 mg of photoinitiator 2-hydroxy-2-methyl-1-phenylacetone, shake and mix, pour into a polytetrafluoroethylene plate, and polymerize under a UV lamp with a wavelength of 365 nm for 0.5 h. After the polymerization reaction is completed, remove the diaphragm from the polytetrafluoroethylene plate and dialyze in deionized water for 24 h. During this period, change the water 8-12 times to ensure that the sodium chloride is completely removed. After dialysis, soak in a 2 mol / L zinc sulfate solution for 24 h. During this period, change the zinc sulfate solution four to five times to finally obtain an electrolyte diaphragm.

[0063] Figure 4 This is the stress-strain curve of the electrolyte membrane of this comparative example, named PND. The stress is only 0.7 MPa, and the strain can only reach 200%, indicating that the mechanical properties of the electrolyte membrane are poor.

[0064] Figure 6 This is the AC impedance spectrum of the electrolyte membrane of this comparative example, named PND. Figure 6 As can be seen, the electrolyte membrane can be tested by clamping it with a stainless steel gasket. The thickness of the membrane is 0.0486 cm, and the resistance is 52.8 Ω. After calculation, the conductivity of the membrane is 4.7x 10 -4 S / cm, indicating that the interfacial impedance of the electrolyte-electrode interface of the electrolyte membrane is large and the ionic conductivity is low.

[0065] (2) The electrolyte membrane obtained in step (1) is placed on a clean polytetrafluoroethylene plate and naturally air-dried until the water content is less than 30%. After the drying, the electrolyte membrane is cut into 14 mm round pieces and assembled into a zinc ion battery for relevant electrochemical tests. The assembly order is: negative electrode shell, zinc sheet, electrolyte membrane, zinc sheet, gasket, spring piece, positive electrode shell.

[0066] Figure 7 The electrolyte membrane of this comparative example is assembled into a zinc ion battery at 1mA / cm 2 The constant current charge and discharge curve tested at a current density of Figure 7 It can be seen that the polarization voltage is very large and the interface is extremely unstable. The voltage suddenly changes after only more than 200 hours of circulation, causing the battery to short circuit.

[0067] Fig. 9 The electrolyte membrane of this comparative example is assembled into a zinc ion battery at 1mA / cm 2 The SEM image of the zinc negative electrode surface after cycling for 200h at a current density of Fig. 9 It can be seen from the figure that there is uneven zinc ion deposition and zinc dendrite formation on the electrode.

[0068] Comparative Example 2

[0069] This comparative example uses a commercial separator GF, model CR2032, and assembles a zinc ion battery for relevant electrochemical tests. The assembly order is: negative electrode shell, zinc sheet, commercial separator, zinc sheet, gasket, shrapnel, positive electrode shell.

[0070] Figure 4 This is the stress-strain curve of the commercial diaphragm of this comparative example, named GF. The stress is only 0.4 MPa and the strain can only reach 20%, indicating that the commercial diaphragm can be easily punctured by dendrites during the battery cycle.

[0071] Figure 5 This is the AC impedance spectrum of the commercial diaphragm of this comparative example, named GF. The commercial diaphragm can be tested by clamping it with a stainless steel gasket. The thickness of the commercial diaphragm is 0.0404cm, the resistance is 4.5Ω, and the conductivity is calculated to be 4.6x10 -3 S / cm.

[0072] Figure 7 The commercial separator of this comparative example is assembled into a zinc ion battery at 1mA / cm 2 The constant current charge and discharge curve tested at a current density of Figure 7 It can be seen that although the polarization voltage is very small, due to the poor mechanical properties and the lack of ion transfer channels, it is easily punctured by the produced dendrites. The glass fiber can only be punctured after more than a hundred hours of circulation, causing a short circuit in the battery.

[0073] Fig.10 The commercial separator of this comparative example is assembled into a zinc ion battery at 1mA / cm 2 The SEM image of the zinc negative electrode surface after cycling for 200h at a current density of Fig.10 It can be seen from the figure that there is a large area of ​​uneven zinc ion deposition and dendrite growth on the electrode.

[0074] In summary, the addition of two-dimensional polymer carboxylate to the gel polymer electrolyte membrane of the present invention enhances ionic interaction, improves the mechanical properties of the gel polymer electrolyte membrane, forms a long-range ordered anion and cation transfer channel, and makes the membrane have a higher ionic conductivity (1.7 x 10 -3 S / cm); and the gel polymer electrolyte membrane of the present invention has a certain self-healing property, and has a certain recovery ability after being punctured by dendrites, which can improve the battery cycle life; the gel polymer electrolyte membrane is assembled into a zinc ion battery, which can effectively inhibit the generation of dendrites and the occurrence of side reactions during the charge and discharge cycle, thereby improving the battery cycle life.

[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a gel polymer electrolyte membrane, characterized in that: The method comprises the following steps: blending a two-dimensional polymer carboxylate with a hydrophilic monomer, adding a crosslinking agent and a first initiator thereto, and reacting under light conditions to obtain a film; dialyzing and soaking the film to obtain a gel polymer electrolyte membrane; The preparation method of the two-dimensional polymer carboxylate is as follows: 3,5-diaminobenzoic acid and acryloyl chloride are subjected to a substitution reaction to obtain a monomer DBA; p-aminobenzoic acid and acryloyl chloride are subjected to a substitution reaction to obtain a monomer ADA; the monomers DBA and ADA are mixed, and an organic base and a second initiator are added thereto to carry out a polymerization reaction to obtain the two-dimensional polymer carboxylate.

2. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The hydrophilic monomer includes a cationic monomer and an anionic monomer. The cationic monomer includes one of acryloyloxyethyltrimethylammonium chloride, acrylamidomethylpropane sulfonic acid and vinyl pyridine; the anionic monomer includes one of sodium styrene sulfonate and 2-acrylamido-2-methylpropane sulfonic acid.

3. The clamping device for high temperature resistance test of lithium battery according to claim 1, characterized in that: The crosslinking agent includes one of divinylbenzene, diisocyanate and N,N-methylenebisacrylamide.

4. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The first initiator includes one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

5. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The organic base is 1,1,3,3-tetramethylguanidine; and the second initiator is potassium persulfate.

6. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The cross-linking agent accounts for 0.5% of the mass of the hydrophilic monomer.

7. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The first initiator accounts for 0.8% of the mass of the hydrophilic monomer.

8. The method for preparing a gel polymer electrolyte membrane according to claim 1, characterized in that: The illumination condition is under ultraviolet light with a wavelength of 365nm.

9. A gel polymer electrolyte membrane, characterized in that: The gel polymer electrolyte membrane is prepared according to the preparation method of any one of claims 1 to 8.

10. A zinc ion battery, characterized in that: The invention comprises a positive electrode, a separator and a negative electrode, wherein the separator is the gel polymer electrolyte separator according to claim 9.

Citation Information

Patent Citations

  • Flexible zinc-air battery gel electrolyte as well as preparation method and application thereof

    CN112563627A

  • Preparation method of high-toughness gel electrolyte and all-solid-state zinc-air battery with firm interface

    CN112886100A

  • Zinc ion battery gel electrolyte and preparation and application thereof

    CN117013104A

  • Polymer electrolyte

    JP1998125134A

  • Method for preparing solid-state polymer zinc-air battery

    US20030228522A1